Pengembangan Sistem Informasi Penelitian menuju World Class University: Kasus di Universitas Diponegoro Tahun 2015-2024 - Handayani, Tri; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: The development of Research Information Systems in higher education institutions is a strategic step toward achieving the status of a World Class University (WCU) and World Class Research University (WCRU).Objective: This article explains the development of the Research, Publication, and Community Service Information System (SIP3MU) at Diponegoro University, which is designed to comprehensively monitor and evaluate faculty performance in research, publication, and community service.Methods: This study employs a qualitative method with a case study approach through observations and interviews involving the leadership and staff of the LPPM UNDIP. The development process of SIP3MU is analyzed using the Waterfall model of information system development.Results: The results indicate that SIP3MU integrates various aspects of the university’s tridharma activities to enhance efficiency, transparency, and accountability in research and community service. The system enables real-time monitoring of faculty work progress, facilitates the management of research data and scientific publications, and supports efforts to improve the quality and quantity of research outputs that meet societal needs. SIP3MU also plays a role in establishing a structured and collaborative research ecosystem at UNDIP. However, evaluations regarding data security and completeness are still necessary to ensure that SIP3MU contributes to UNDIP’s vision of becoming both a World Class University (WCU) and a World Class Research University (WCRU).Conclusion: SIP3MU, developed by LPPM UNDIP, is a system designed to record and manage research and community service activities in line with the standards of Indonesia's Ministry of Research, Technology, and Higher Education, supporting UNDIP's vision as a leading research university, enhancing management effectiveness, national and international reputation, and requiring continuous evaluation to ensure transparency, accountability, and global collaboration.